Human capital, innovation capability and economic growth in Portugal, 1960–2001 - Teixeira, Aurora A.C. (2018)
In maintaining that the main flaw in empirical studies on economic growth derives from the fact that they employ Solow-style neoclassical growth models, rather than testing actual endogenous growth theory, we examine the human capital-innovation-growth nexus, thus testing new growth theory more directly.We test its insights against the economic evolution of an individual country, Portugal, using time series data from 1960 to 2001. Estimates based on vector autoregressive and cointegration analysis seem to confirm that human capital and indigenous innovation efforts were enormously important to the economic growth process in Portugal during the period of study. In particular, the indirect effect of human capital through innovation, emerges here as being critical, showing that a reasonably high stock of human capital is necessary to enable a country to reap the benefits of its indigenous innovation efforts.